مقومات الداعية المسلم الشيخ محمد الغزالي انموذجا - عوادي, خولة (University of Eloued-جامعة الوادي, 2022)
"تقوم هذه الرسالة على البحث في الفكر الدعوي الإسلامي عند الشيخ محمد الغزالي، وتكمن أهمية الدراسة في أنها تسلط الضوء على حياة العالم المفكر الشيخ محمد الغزالي، وآثاره العلمية. واتبعت في هذه الدراسة المنهج الوصفي، وتهدف هذه الدراسة إلى الاطلاع على حياة الشيخ الغزالي وما يتعلق بها من ميلاده ونسبه وشيوخه وتراثه العلمي، ثم الكشف عن فكره الدعوي الإسلامي. هذا وقد أظهرت الدراسة أن الشيخ الغزالي ذو فكر تجديدي، وسطي، وأن فكره الدعوي يمكن الاستفادة منه في مجال الدعوة المعاصرة، كما أبرزت الدراسة المكانة العلمية المرموقة التي تبوأها، وركزت الدراسة على مقومات وأساليب الدعوة عند الشيخ الغزالي وشروط الاصلاح الدعوي عنده. وقد تضمنت هذه الدراسة الكثير من النتائج والتي من أهمها: أن الشيخ الغزالي كان داعية كبيراً، وأنّ من أهم المجالات التي عالجها بفكره المجال الدعوي، وأن الدعوة عند الشيخ الغزالي تنوّعت أساليبها، وأن الشيخ الغزالي أحدث جدلاً واسعاً بطرح بعض الأفكار الجريئة مدافعاً عنها بكل قوة. ""This thesis is based on researching the Islamic advocacy thought of Sheikh Muhammad Al-Ghazali The importance of the study is that it sheds light on the life of the thinker Sheikh Muhammad Al-Ghazali, and his effects Scientific. In this study, I followed the descriptive approach, and this study aims to see the life of Sheikh Al-Ghazali and what is related to it from his birth, lineage, elders and scientific heritage, and then reveal his Islamic advocacy thought. The study showed that Sheikh Al-Ghazali has a modernist, moderate thought, and that his advocacy thought can be Benefiting from it in the field of contemporary advocacy, and the study also highlighted the prestigious scientific position that. He assumed it, and the study focused on the elements and methods of advocacy according to Sheikh Al-Ghazali and the conditions for advocacy reform with him. This study included many results, the most important of which are: Sheikh Al-Ghazali was a caller "
مذكرة ماستر
Keywords: الرسالة , الفكر الدعوي الإسلامي , الدراسة; researching related Benefiting